The mediating effect of self-efficacy on the relationship between self-care ability and disability level in older adult patients with chronic diseases - Wang, Tiemei; Wang, Senlin; Wu, Nianwei; Liu, Yan (Frontiers in Public Health, 2024)
Objective This study investigates the mediating effect of self-efficacy on the relationship between self-care ability and disability level in older adult patients with chronic diseases. Methods A convenience sampling method was used to select 372 older adult patients with chronic diseases from five tertiary hospitals in Chengdu, Sichuan Province. General demographic information was collected using a questionnaire, and self-efficacy, self-care ability, and disability were assessed using standardized scales. Data were analyzed using SPSS 26.0, and the PROCESS macro was employed to test the mediating effect of self-efficacy. Results The mean score for self-efficacy was 26.09 ± 7.20, for self-care ability was 113.19 ± 23.31, and for disability was 154.19 ± 29.32. Self-efficacy was positively correlated with self-care ability (r = 0.73, p < 0.001. and negatively correlated with disability (r = −0.84, p < 0.001. and self-care ability and disability (r = −0.91, p < 0.001.. The indirect effect of self-efficacy on the relationship between self-care ability and level of disability was −0.03 (95% CI −0.08 to −0.04), accounting for 16.67% of the total effect. Conclusion Self-efficacy partially mediates the relationship between self-care ability and disability in older adult patients with chronic conditions. Healthcare providers can improve self-care behaviours and self-efficacy in older adult patients through effective interventions to reduce the incidence of disability.